2004
DOI: 10.1163/156856204322793548
|View full text |Cite
|
Sign up to set email alerts
|

Drug release from polyureaurethane coating modified by plasma immersion ion implantation

Abstract: A crosslinked polyurethanurea (PUU) coating was synthesised from a solution on metal vascular stents. In the model system the glucocorticoid prednisolone was inserted into the film by the equilibrium swelling method; after this plasma immersion ion implantation (PIII) was applied to modify the coating for improved release kinetics. This treatment causes the formation of oxygen-containing and unsaturated carbon-carbon groups in the PUU and a destruction of the drug in the surface layer. As a consequence, the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Nonthrombogenicity and the prevention of intimal hyperplasia are two critical features desired in polymer-coated, drug-eluting, vascular stents. Elastomeric polyurethanes have served as coating materials for vascular expandable stents due to their high distensibility, processability, and biocompatibility. Nonthrombogenic moieties, such as PC, , sulfobetain, sulfate, , and poly(ethylene glycol), have been physically and chemically combined with polyurethanes broadly intended for cardiovascular application in an effort to improve their blood compatibility. Among these, PC has been most frequently studied.…”
Section: Discussionmentioning
confidence: 99%
“…Nonthrombogenicity and the prevention of intimal hyperplasia are two critical features desired in polymer-coated, drug-eluting, vascular stents. Elastomeric polyurethanes have served as coating materials for vascular expandable stents due to their high distensibility, processability, and biocompatibility. Nonthrombogenic moieties, such as PC, , sulfobetain, sulfate, , and poly(ethylene glycol), have been physically and chemically combined with polyurethanes broadly intended for cardiovascular application in an effort to improve their blood compatibility. Among these, PC has been most frequently studied.…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that PU coatings can improve endothelialization [171]. PU has also been investigated in drug delivery systems [172][173][174]. Lambert et al [172] successfully studied the drug release kinetics and distribution of the model drug Forskolin delivered from the PU coated metallic stents.…”
Section: Copolymersmentioning
confidence: 99%
“…Ion‐beam implantation and PIII have been used for the modification of polyethylene, 13–21 polystyrene, 22–28 polytetrafluoroethylene, 29–34 poly(ethylene terephthalate), 35–38 poly(methyl methacrylate), 39–42 polyurethane, 43–47 and other polymers. Leading to increases in the hardness, electrical conductivity, and wettability, structural changes typical of ion‐irradiated polymers, such as carbonization, depolymerization, and oxidation, have been observed.…”
Section: Introductionmentioning
confidence: 99%